INDONESIA DAN KERJA SAMA FOREST LAW ENFORCEMENT GOVERNANCE AND TRADE – VOLUNTARY PARTNERSHIP AGREEMENT (FLEGT-VPA) DALAM MENANGANI PERDAGANGAN KAYU ILEGAL DI INDONESIA - Rahanti, Sari Saptuning; Windiani, Reni; Wahyudi, Fendy Eko (Journal of International Relations, 2016)
Illegal logging is an environmental issue that is becoming one of the majorfocus of the international agendas. Losses due to illegal logging not onlyaffects the environment sector but also in the economic, legal and social sector.As one of the largest wood exporting countries for the European Union,Indonesia holds an important role in addressing illegal logging in both theEuropean Union and in Indonesia itself. In addressing the issue, Indonesia andthe European Union establish a cooperation framework called the Forest LawEnforcement Governance and Trade - Voluntary Partnership Agreement (VPA).This study research seeks to analyze Indonesia’s background in it’sparticipation on FLEGT – VPA -that is pioneered by the European Union as- aframework in preventing cases of illegal logging in Indonesia, as one of themajor exporters of the European Union. This study reseach is usingqualitative-descriptive method. This study research also uses the theory ofinternational regimes of Snidal. The results of this study research proves thatthe collaboration regime of FLEGT-VPA had a positive impact on reducing thenumbers of illegal logging and increasing the export number from Indonesia.